A Switched-Capacitor Bidirectional DC-DC Converter with Wide Voltage Gain Range for Electric Vehicles with Hybrid Energy Sources - Dr. K.Suneeta; Mr. N.Laxman; Mr. B.Sreenu (The journal of contemporary issues in business and government, 2017)
An exchanged capacitor bidirectional DC-DC converter with a high advance up/step-down voltage gain is proposed for electric vehicles (EVs) with a half breed vitality source framework (HESS). The converter displayed has the benefits of being a basic circuit, a diminished number of parts, a wide voltage-gain extend, a low voltage stress, and a shared opinion. Likewise, the synchronous rectifiers permit zero voltage exchanging (ZVS) turn-on and turn-off without requiring any additional equipment, and the proficiency of the converter is improved. A 300W model has been created which approves the wide voltage-gain scope of this converter utilizing a variable low-voltage side (40V- 100V) and to give a consistent high-voltage side (300V). The greatest effectiveness of the converter is 94.45% in step-down mode and 94.39% in step-up mode. The test results additionally approve the possibility and the adequacy of the proposed topology.